Penguatan Kesadaran Hukum di Kalangan Siswa SMAN 1 Telaga Sebagai Upaya Pencegahan Pelanggaran Hukum Sejak Dini: Pengabdian - Sastro M. Wantu; Nopiana Mozin; Rendi R Toma (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The collaborative community service program conducted by lecturers and students of the Civic Education Department, Faculty of Social Sciences, Gorontalo State University, aimed to strengthen legal awareness among students of SMA Negeri 1 Telaga as an effort to prevent legal violations from an early age. This program was motivated by the low level of students’ understanding of legal values, as identified through preliminary observations. The implementation adopted a participatory approach that emphasized students’ active involvement in various educational activities, including legal counseling, group discussions, case simulations, and digital-based legal awareness campaigns. The stages of implementation consisted of preparation (needs analysis, activity planning, and coordination with the school) and execution (legal education sessions, integration into learning activities, extracurricular programs, and evaluation). The results indicated a significant improvement in students’ legal knowledge and attitudes, where they began to perceive law not merely as a coercive instrument but as a moral and social guideline that ensures order and justice. Moreover, students demonstrated behavioral changes toward greater discipline, responsibility, and awareness of the legal consequences of their actions. This program shows that civic education effectively fosters strong legal character and serves as a foundation for developing young generations who are law-abiding, have integrity, and contribute positively to society and the natio.